PARTICIPATING IN GODLINESS: A STUDY OF THE LAWS CONCERNING THE SOCIALLY MARGINALIZED IN THE TORAH - Hussain, Jamie (My University, 2008)
Taking a canonical approach to the text of the Old Testament, this thesis highlights the compassion of God by examining the social justice laws in the Torah. These laws governing Israel's behaviour toward its socially marginalized population show God's concern for, and involvement in, human affairs. Arising from these laws are the three themes of protection, provision, and inclusion, which summarize the advocacy of God on behalf of the socially marginalized. As a people redeemed by God out of a life of slavery, Israel experienced God's gracious advocacy first hand. As a people in covenant relationship with God, Israel would live before God and in accordance with his laws. Motivated by their gratefulness to God, Israel's obedience to these social justice laws would enable them to behave God-like in their behaviour toward the oppressed in their society, subsequently showing forth the compassion of God that protects, provides and includes.
Keywords: Religion; Religion